Synthesis of Amino‐Substituted Pyrrole‐Fused Perylenebis(dicarboximide) Derivatives by a One‐Pot Azidation/Reduction/Cyclization. Issue 31 (13th September 2013) - Li, Yongjun; Xu, Liang; Jiang, Runsheng; Liu, Huibiao; Li, Yuliang
Abstract: Amino‐substituted pyrrole‐fused perylenebis(dicarboximides) have been prepared from tri‐ or tetrabromoperylene prcursors by using the classical azidation conditions for the substitution of aromatic halogen, that is, NaN3, sodium ascorbate, CuI, and N, N ‐dimethylethane‐1, 2‐diamine in DMSO/H2 O. The pyrrole‐fused dyes are highly photochemically and thermally stable, which may be useful for labelling and as building blocks for the synthesis of functional molecular materials. Abstract : A facile method for synthesizing amino‐substituted pyrrole‐fused perylenebis(dicarboximides) starting from tri‐ or tetrabromoperylenebisimide has been developed by using the classical azidation conditions for the substitution of aromatic halogen. These pyrrole‐fused dyes display strong optical properties, efficient redox properties, and high thermal stability.